Computational Biomechanics for Medicine Soft Tissues and the Musculoskeletal System - Wittek, Adam.; Nielsen, Poul M.F.; Miller, Karol; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
One of the greatest challenges for mechanical engineers is to extend the success of computational mechanics to fields outside traditional engineering, in particular to biology, biomedical sciences, and medicine. The proposed workshop will provide an opportunity for computational biomechanics specialists to present and exchange opinions on the opportunities of applying their techniques to computer-integrated medicine. Computational Biomechanics for Medicine: Soft Tissues and the Musculoskeletal System collects the papers from the Medical Image Computing and Computer Assisted Intervention conference (MICCAI 2010) in Beijing, dedicated to research in the field of medical image computing and computer assisted medical interventions. The topics covered include: medical image analysis, image-guided surgery, surgical simulation, surgical intervention planning, disease prognosis and diagnostics, injury mechanism analysis, implant and prostheses design, medical robotics.
Keywords: Engineering; Surgery; Engineering mathematics; Materials; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Biophysics and Biological Physics; Biomaterials; Appl.Mathematics/Computational Methods of Engineering; Continuum Mechanics and Mechanics of Materials; Surgery